Spatio-temporal distribution and environmental risk of sedimentary heavy metals in the Yangtze River Estuary and its adjacent areas - Chen, B.; Liu, J.; Qiu, J.; Zhang, X.; Wang, S.; Liu, Jian (Elsevier, 2017)
© 2016 Twenty-five surface sediments and one sediment core sample were collected from the study area. Grain size, major elements, and heavy metals were determined. The content of fine-grained sediments (silt and clay), as well as the concentrations of major elements and heavy metals, showed seaward decreasing trends, with high content in the coastal areas of the East China Sea (ECS) and south west of Jeju Island. Low enrichment factor (EF) and geoaccumulation index (Igeo) values were found, indicating that the ecological risk of heavy metals was low. The EF values obtained from the high-resolution sedimentary records of heavy metals in the Yangtze River Estuary could be divided into Stage 1 (1950s to the late 1970s) and Stage 2 (late 1970s to the current sampling day), which coincided with economic development of the Yangtze River Basin, implementation of environmental protection, and impoundment of the Three Gorges Dam.